Income inequality and 30 day outcomes after acute myocardial infarction, heart failure, and pneumonia: retrospective cohort study - Lindenauer, Peter K (BMJ Publishing Group Ltd., 2013)
Objectives To examine the association between income inequality and the risk of mortality and readmission within 30 days of hospitalization. Design Retrospective cohort study of Medicare beneficiaries in the United States. Hierarchical, logistic regression models were developed to estimate the association between income inequality (measured at the US state level) and a patient’s risk of mortality and readmission, while sequentially controlling for patient, hospital, other state, and patient socioeconomic characteristics. We considered a 0.05 unit increase in the Gini coefficient as a measure of income inequality. Setting US acute care hospitals. Participants Patients aged 65 years and older, and hospitalized in 2006-08 with a principal diagnosis of acute myocardial infarction, heart failure, or pneumonia. Main outcome measures Risk of death within 30 days of admission or rehospitalization for any cause within 30 days of discharge. The potential number of excess deaths and readmissions associated with higher levels of inequality in US states in the three highest quarters of income inequality were compared with corresponding data in US states in the lowest quarter. Results Mortality analyses included 555 962 admissions (4348 hospitals) for acute myocardial infarction, 1 092 285 (4484) for heart failure, and 1 146 414 (4520); readmission analyses included 553 037 (4262), 1 345 909 (4494), and 1 345 909 (4524) admissions, respectively. In 2006-08, income inequality in US states (as measured by the average Gini coefficient over three years) varied from 0.41 in Utah to 0.50 in New York. Multilevel models showed no significant association between income inequality and mortality within 30 days of admission for patients with acute myocardial infarction, heart failure, or pneumonia. By contrast, income inequality was associated with rehospitalization (acute myocardial infarction, risk ratio 1.09 (95% confidence interval 1.03 to 1.15), heart failure 1.07 (1.01 to 1.12), pneumonia 1.09 (1.03 to 1.15)). Further adjustment for individual income and educational achievement did not significantly attenuate these findings. Over the three year period, we estimate an excess of 7153 (2297 to 11 733) readmissions for acute myocardial infarction, 17 991 (3410 to 31 772) for heart failure, and 14 127 (4617 to 23 115) for pneumonia, that are associated with inequality levels in US states in the three highest quarters of income inequality, compared with US states in the lowest quarter. Conclusions Among patients hospitalized with acute myocardial infarction, heart failure, and pneumonia, exposure to higher levels of income inequality was associated with increased risk of readmission but not mortality. In view of the observational design of the study, these findings could be biased, owing to residual confounding.